Stroke as a Global Health Issue: A Descriptive Analysis of the Theoretical Framework and Scientific Definitions - Husni Husni (Indonesian Journal Publisher, 2026)
This study aims to analyze stroke as a global health problem by examining its theoretical framework, scientific definitions, and underlying mechanisms through a comprehensive descriptive analysis. The research employs a qualitative approach using a descriptive method through a literature study. Data were collected through systematic literature searches and document analysis of credible academic sources, including peer reviewed journal articles and scientific publications discussing stroke epidemiology, risk factors, and pathophysiology. The collected literature was analyzed through qualitative procedures consisting of theme identification, data reduction, conceptual categorization, and inductive interpretation to develop a comprehensive understanding of the phenomenon. The results indicate that stroke remains one of the leading causes of mortality and long term disability worldwide, characterized by complex interactions between vascular dysfunction, metabolic risk factors, and molecular mechanisms such as neuroinflammation, oxidative stress, and neurovascular unit disruption. Hypertension and metabolic disorders were identified as the most significant modifiable risk factors contributing to the increasing global burden of stroke. Furthermore, advances in molecular neuroscience and emerging neurorehabilitation strategies provide new insights into prevention, diagnosis, and recovery processes. These findings highlight the importance of integrated approaches combining preventive healthcare, early detection, and multidisciplinary treatment strategies to address the global impact of stroke. In conclusion, this study contributes to strengthening the theoretical understanding of stroke as a multidimensional health issue and provides a conceptual foundation for future research and policy development in global health and cerebrovascular disease management.